BCI Sensor Based Environment Changing System for Immersion of 3D Game - Ok-Hue Cho; Won-Hyung Lee (International Journal of Distributed Sensor Networks)
We present a methodology about game environment system based on BCI (brain computer interface) for immersion of FPS game play. FPS game is a video game genre centered on gun shooting and projectile weapon-based combat through a first-person perspective; immersion is important factor in this game. FPS game designer makes efforts to raise player's immersion using interface, graphic effect, sound, and so forth. We implemented real-time game environment system using game player's emotional state information from the BCI sensor to raise the degree of immersion in FPS game. We measured user's EEG signal using MindSet to take user's emotional state on playing game. We can get user's emotional state in 4 categories (attention/inattention, meditation/uneasiness) and this emotional state interacts with game environment system real time. In game environment space, each player experiences different environmental situation (lighting, fog) because each player has emotional state on each scene. We implemented game environment system to be changed (lighting, fog) on playing FPS game. Player can feel the change of game environment by our system. We found out that game environment system can be applied to various game genres to raise player's immersion on playing game.